Kualitas Konten Digital Marketing Dan Pengaruhnya Terhadap Brand Image Dan Keputusan Pembelian Konsumen Di Kota Denpasar - Ni Kadek Sri Rita Indriyani; Ni Luh Ketut Ayu Sudha Sucandrawati; Ni Putu Andini Desiyanti Laksmi (Universitas Pahlawan Tuanku Tambusai, 2022)
Digital marketing content is one of the marketing tools that can utilize social media as a place to promote a product through a digital content with quality which later on the promotion can affect the brand image of a product and make target consumers lead to consumer purchasing decisions. This study aims to determine the variable quality of digital marketing content and its influence on brand image and consumer purchasing decisions in the city of Denpasar. The samples used in this study were 109 samples and this research was conducted on the Babi Guling culinary SMEs in the Denpasar city. The method used in this study is a quantitative method using a questionnaire distribution instrument that has been processed and tested for reliability, validity, classical assumptions, regression analysis test and path analysis with Sobel test. The results of data processing obtained by this study that have been processed with SPSS obtained the following results: the variable quality of digital marketing content does not have a significant positive effect on consumer purchasing decisions in the city of Denpasar, the quality of digital marketing content has a significant effect on brand image, brand image has a significant positive effect on consumer purchasing decisions, and brand image is able to mediate the influence between the quality of digital marketing content on consumer purchasing decisions in the city of Denpasar. Keywords: Digital marketing content quality, brand image, consumer purchasing decisions